The Evaluative Analysis Of Tahfidz Al-Qur’an Program at School: A Multisite Study at Junior High School of Pesantren Around Ponorogo - Choiri, Moh. Miftachul; Mujahidin, Anwar; Ju’subaidi, Ju’subaidi; Samsudin, Mohamad Aso; Hasanah, Hasanah (Universitas Yudharta Pasuruan, 2024)
Evaluative study is a type of research to identify the relationship between goals, processes, results, and the impact of the implementation of a certain program or activity. The current research aimed to evaluate the program of tahfidz (Qur’an memorization) in several junior high schools of pesantren (SMP Pesantren) around Ponorogo Regency. It is qualitative research with multisite study. The informants were selected by purposive and snowball sampling techniques. Data were collected through in-depth interviews, participatory observation, and documentation. They were analyzed using the interactive technique of Miles and Huberman, which included data reduction, data display, and conclusion drawing. The results suggested that tahfidz program at schools of pesantren in Ponorogo can improve the students' morale. The program was implemented through activities integrated with the learning process. However, some schools separate the program (takhassus). Besides, the tahfidz program at junior high school of pesantren is intended that they graduate with a complete memorization of the Qur’an. The positive impact is an increase in public interest and trust in the school while the negative impact is the competition to increase the number of memorizations that is not based on the ability of students so that they encounter stress.